Prostatic Abscess a Diagnostic Dilemma - Agarwal, A; Praveen, C R; Hirachan, S; Karmacharya, A; Belokar, W K (Journal of Nepal Health Research Council, 2011)
Abscess of the prostate has become increasingly rare due to modern antibiotics and a decreasing incidence of gonococcal infections. It is still difficult to diagnose the disorder on clinical grounds. Diagnosis is often made after Ultrasound examination. We report 2 cases of prostatic abscess and review etiopathogenic factors, clinical findings, diagnosis and treatment of this uncommon entity. Â  Key words: abscess, diagnosis,etiopathogenesis,prostate, therapeutics